2021
DOI: 10.1016/j.chemosphere.2020.128090
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics and their associated organic pollutants from the coastal waters of the central Adriatic Sea (Italy): Investigation of adipogenic effects in vitro

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 79 publications
(90 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, coastal waters site was an open marine environment, less subject to human activity pressure, which could explain the lower particle abundances at this site. These last remained similar with other studies using the Manta net to collect MPs in coastal waters, as for example in the southwest coast of India (1.25 ± 0.88 particles/m 3 ) and in the central Adriatic sea (0.04 ± 0.01 to 3.42 ± 2.28 particles/m 3 ), but higher than that recorded in coastal Arctic fjords (0.06 particles/m 3 ) and Cilacap coast in Indonesia (0.27–0.54 particles/m 3 ) ( Robin et al., 2020 ; Capriotti et al., 2021 ; Carlsson et al., 2021 ; Syakti 2017 ).…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, coastal waters site was an open marine environment, less subject to human activity pressure, which could explain the lower particle abundances at this site. These last remained similar with other studies using the Manta net to collect MPs in coastal waters, as for example in the southwest coast of India (1.25 ± 0.88 particles/m 3 ) and in the central Adriatic sea (0.04 ± 0.01 to 3.42 ± 2.28 particles/m 3 ), but higher than that recorded in coastal Arctic fjords (0.06 particles/m 3 ) and Cilacap coast in Indonesia (0.27–0.54 particles/m 3 ) ( Robin et al., 2020 ; Capriotti et al., 2021 ; Carlsson et al., 2021 ; Syakti 2017 ).…”
Section: Resultsmentioning
confidence: 93%
“…At the European level, such pollutant was included among the 11 qualitative descriptors of the Marine Strategy Framework Directive upon which the quality of the marine environment is assessed (European Parliament, 2008/56/EC). Since 2004, when the term microplastic was coined, extensive research has demonstrated the ubiquity of plastic pollution in several matrices such as beaches (Fortibuoni et al, 2021;Prevenios et al, 2018), sediments (Piazzolla et al, 2020;Renzi et al, 2018) and seawater (Atwood et al, 2019;Capriotti et al, 2021) -regardless of how remote they are (Cincinelli et al, 2017;Lusher et al, 2015). Microlitter was retrieved from all water samples taken within the framework of the PISCES project in a much higher (~20-fold) average concentration (0.30 ± 0.02) than litter particles > 5 mm (0.014 ± 0.003 items/m³).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 60 original articles were read in full and then 20 papers were removed with reason, as reported in Table S1 . In total, 40 studies met the selection criteria and were included in this review [ 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%